2022
DOI: 10.4081/jphr.2021.2736
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Efforts to Maintain Competence: A Qualitative Study

Abstract: Background: The clinical competence of nurses should be maintained to ensure patient safety. Competence is the integration of knowledge, skills, and attitudes. Nurse competency also improves the quality of nursing care and reduces the incidence of missed nursing care. This study aimed to explore the experiences of nurses maintaining a nurse competence system in hospitals through continuing education.Design and Methods: The research method used was qualitative phenomenological research, and the data was collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 20 publications
0
5
0
3
Order By: Relevance
“…The interview sample consisted of 14 nurses aged 35.8 ± 4.46 years (range 27-42) who had 13.4 ± 4.07 years of work experience (range [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The characteristics of the other samples are listed in Table 5.…”
Section: Qualitative Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interview sample consisted of 14 nurses aged 35.8 ± 4.46 years (range 27-42) who had 13.4 ± 4.07 years of work experience (range [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The characteristics of the other samples are listed in Table 5.…”
Section: Qualitative Resultsmentioning
confidence: 99%
“…Career advancement provides opportunities for nurses to enhance their competencies by participating in professional development programmes [ 5 ]. Continuing professional development (CPD), as part of career advancement, is essential for career progression and maintenance of nursing competency [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Rahmah et al [ 31 ] demonstrated that a competent nurse may improve the quality of the care delivered and reduce incidences of missed nursing care. Chaboyer et al [ 32 ] reported that increased patient-adverse events were associated with poor quality of care, while similar research indicated that meeting human needs through accountability, advocacy, and empathy is essential for the provision of quality nursing care in practice [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the nurses who work in the ICU are not ICU nurses and 19% of those who receive an introduction to the ICU COVID-19 (Bergman et al, 2021). Head nurses need to increase training opportunities for implementing nurses to increase competence in providing care to patients (Rahmah et al, 2022;Suhariyanto et al, 2018).…”
Section: Discussionmentioning
confidence: 99%